Optical Coherence Tomography Predictors of Favorable Functional Response in Naïve Diabetic Macular Edema Eyes Treated with Dexamethasone Implants as a First-Line Agent. (24th March 2021) - Meduri, Alessandro; Oliverio, Giovanni William; Trombetta, Luigi; Giordano, Marta; Inferrera, Leandro; Trombetta, Costantino John
Abstract : Purpose . To evaluate efficacy and safety of intravitreal dexamethasone 0.7 mg implant in treatment-naïve DME patients and to assess the utility of OCT structural biomarkers as predictors of functional response after treatment. Methods . Thirty-nine eyes of 39 diabetic patients with center involving DME were enrolled. Best-corrected visual acuity (BCVA) and SS-OCT (DRI SS-OCT Triton, Topcon, Japan) to evaluate central retinal thickness (CRT), serous retinal detachment (SRD), intraretinal cysts (IRC), number of hyper-reflective spots (HRS), integrity of the ellipsoid zone (EZ), disorganization of the inner retinal layers (DRIL), vitreomacular adhesion (VMA), vitreomacular traction (VMT), and posterior vitreous detachment (PVD) were evaluated at baseline and at 3, 6, and 12 months after treatment. Multiple logistic analysis was performed to evaluate the possible OCT biomarker as predictive factors for final visual acuity improvement at the end of treatment. Results . At 12 months after treatment, the mean BCVA improved from 51.6 ± 17.5 to 56.9 ± 17.3 ETDRS letters (p = 0.03 ). Furthermore, there were statistically significant changes in CRT, IRC, HRS, and SRD. Nineteen patients presented a >10-letters improvement in BCVA; the presence of SRD at baseline was a predictor of good functional treatment response at 12 months (OR 2.1; 95% C.I. 1.2–4.9; p = 0.001 ) as well as the presence of EZ integrity preoperatively (OR 1.3; 95% C.I. 0.5–2.4; p = 0.001 ) and the absence of vitreoretinal interface alteration (OR 1.1; 95% C.I. 0.3–2.3; p = 0.02 ). No significant changes in the IOP and lens status were observed throughout the follow-up period. Conclusion . This study empathized the importance of structural biomarkers as predictors of favorable response and confirmed the efficacy and safety of intravitreal dexamethasone implant in treatment-naïve DME patients showing a better functional response in the presence of SRD integrity of EZ and absence of vitreoretinal alterations.